Abundance of humpback whales on the Abrolhos Bank wintering ground, Brazil - Freitas, Ana C; Kinas , Paul G.; Martins , Cristiane C. A.; Engel, Marcia H. (J. Cetacean Res. Manage., 2023)
Abundance estimates are presented for the humpback whales wintering off Brazil which ‘visit’ a surveyed area off Abrolhos Bank and display fluke-exposing behaviour. The study is based on photo-identification data collected between 1996 and 2000. Chapman-corrected Petersen estimates for all pairs of data result in estimates from 1,948 individuals up to 3,001 with coefficients of variation around 0.25. A more elaborate closed population multiple-recapture maximum-likelihood estimate is 2,393 with 95% profile-likelihood confidence interval (CI=1,924, 3,060). Replacing the closed-population assumption with a population allowed to grow (or decrease) according to some constant rate over the study period, the maximum-likelihood estimate of population size for the year 2000 becomes 3,871 (CI=2,795, 5,542) associated to an estimated annual growth rate of 31% over the study period and in the surveyed area. Although the inclusion of the growth rate results in a less restrictive assumption about population size, it is unclear at this time how to interpret it since the population around the Abrolhos Bank is some (unknown) fraction of whales wintering off Brazil. Alternatively, a fit of Whitehead’s model allowing for emigration and re-immigration gives an estimate of about 3,000 whales (CI=2,500, 3,650).